Answer:
[tex](6x^2- 5x + 5)[/tex] should be subtracted from [tex]7x^2- 6x+5 [/tex] to get the difference equal to [tex] x^2 - x[/tex]
Step-by-step explanation:
Here, the given polynomial [tex]P(x) = 7x^2- 6x+5 [/tex]
And, The other Polynomial [tex]R(x) = x^2 - x[/tex]
Let us assume there exists a polynomial Q(x) such that the difference of P(x) and Q(x) is R (x):
⇒P(x) - Q(x) = R (x)
[tex]\implies (7x^2- 6x+5) - Q(x) = (x^2 - x)[/tex]
[tex]\implies Q(x) = (7x^2- 6x+5) - (x^2 -x) = 7x^2- 6x+5 - x^2 + x = 6x^2- 5x + 5\\\implies Q(x) = (6x^2- 5x + 5)[/tex]
Hence, [tex](6x^2- 5x + 5)[/tex] should be subtracted from [tex]7x^2- 6x+5 [/tex] to get the difference equal to [tex] x^2 - x[/tex]